Performance assessment and optimization of kenaf fiber reinforced shape memory polymer composites - Khiyon, Nor Hanim (2025)
Rising global concern over environmental degradation and reliance on non-renewable resources has increased demand for sustainable smart materials. Shape memory polymer composites (SMPCs), known for their thermal-trigered shape recovery, are promising but limited by the environmental impact of synthetic reinforcements. This study explores kenaf fiber (KF) as a natural reinforcement in SMPCs, using glass fiber (GF) as a benchmark. A total of 174 specimens were fabricated with shape memory polyurethane (SMPU) at fiber weight percentages of 5%, 10%, 15%, 20%, 25%, 30%, 40%. Characterization included Tensile Test, Thermogravimetric Analysis (TGA), Dynamic Mechanical Analysis (DMA), Thermomechanical Analysis (TMA), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy with Energy Dispersive X-ray (SEM-EDX) was conducted. Response Surface Methodology (RSM) was applied for optimization. Results confirmed a trade-off between KF and GF. GF achieved the highest tensile strength, 39.27 MPa and stiffness, 36.35 GPa whereas KF provided greater ductility and energy absorption, with elongation at break of 4.25% compared to 1.2% for 20GF. Thermal analysis showed higher degradation onset for GF, 303°C compared to KF, 271°C, while DMA indicated superior storage modulus for GF, 7780.9 MPa at 40GF compared to 1927.7 MPa for 30KF. However, KF demonstrated stronger damping which is tan delta of 0.41 and higher shape recovery of 93% at 30KF, while GF achieved better fixity of 75% at 30GF. RSM identified the optimum condition at 25.49% KF and 47.10°C, yielding a storage modulus of 1189 MPa and loss modulus of 215.85 MPa. In conclusion, KF-SMPCs offer competitive mechanical and smart functionality with environmental advantages, making them suitable for semi-structural, vibration sensitive, and adaptive systems in automotive, civil, and aerospace sectors contributing to the development of greener, smarter composite materials.